Analysis of Pregnancy, Labor and Perinatal Outcomes of Women with Pyelonephritis - A. N. Rymashevsky; A. E. Volkov; J. L. Naboka; N. A. Krasnikova; V. V. Markina (Медицинский вестник Юга России, 2011)
Purpose: Assessment of the impact of chronic pyelonephritis (CP) on pregnancy, childbirth and the state of a newborn.Materials and Methods: 64 pregnant women with chronic pyelonephritis (study group). Comparison group consisted of 124 apparently healthy women with physiological pregnancy. In the groups evaluated parity, clinical and laboratory parameters of blood (blood count, hematocrit, leukocyte index of intoxication), during pregnancy, birth, state of the newborn babies and their incidence. To detect virus-bacterial pathogens persisting in the urine of infants born to mothers with HP, examined 42 children. All isolates were determined rates of adhesion and persistence factors (antilizotsim (ALA) and antiinterferon (AIA) activity). In the urine of surveyed defined mycoplasma, chlamydia, herpes simplex virus type I and II, Epstein-Barr virus, cytomegalovirus, and papilloma viruses using standard polymerase chain reaction (PCR).Results: Pregnancy complicated by HP more severe with various complications: anemia and placental insufficiency. In patients with CP were significantly more marked prematurity (6,25% versus 1,6% in the comparison group). In assessing the viral-bacterial infection of the urine of infants born to mothers suffering from CP, 50% of the bacterial population was observed in 50% were identified opportunistic bacteria in an amount not to exceed thresholds.Summary: Chronic pyelonephritis is one of the factors influencing the course of pregnancy. Perinatal morbidity in children born to women who suffer from CP, no more than general population values. Significant correlation between the microflora of mother and child is absent.